Analysis of the characteristic compounds of Citri Sarcodactylis Fructus from different geographical origins. Issue 1 (10th June 2021) - Zheng, Zhenxing; Hu, Hanwen; Zeng, Li; Yang, Huan; Yang, Tianlong; Wang, Di; Zhang, Chuanyang; Deng, Yun; Zhang, Mingzhi; Guo, Dale; Deng, Fang
Abstract: Introduction: Citri Sarcodactylis Fructus (CSF) is widely used as a food ingredient and a traditional Chinese medicine. In China, CSF is cultivated in many places, including Sichuan, Guangdong, Zhejiang, and Fujian provinces. The types and chemical contents of CSF from different origins may vary greatly due to the difference in climate and environmental conditions. Therefore, comparing the chemical composition of CSF from various places is vital. Objective: To rapidly select potential characteristic compounds for differentiating CSF from different origins. Material and methods: Thirty‐one batches of CSF samples from different regions were analysed using ultra‐performance liquid chromatography with hybrid quadrupole‐orbitrap high‐resolution mass spectrometry. Thereafter, chemometric methods, including principal component analysis (PCA) and orthogonal partial least squares discrimination analysis (OPLS‐DA), were employed to find differential metabolites among the CSF samples from various origins. Results: PCA revealed 77.9% of the total variance and divided all CSF samples into three categories corresponding to their origins. OPLS‐DA displayed better discrimination of CSF from different sources, with R 2 X, R 2 Y, and Q 2 of 0.801, 0.985, and 0.849, respectively. Finally, 203 differential metabolites were obtained from CSF from different origins using the variable importance in projection of the OPLS‐DA model, 30 of which were identified, and five coumarin compounds were selected as marker compounds discriminating CSF from different origins. Conclusion: This work provides a practical strategy for classifying CSF from different origins and offers a research foundation for the quality control of CSF. Abstract : With the purpose of finding characteristic compounds which can distinguish Citri Sarcodactylis Fructus (CSF) from different regions, we compared differential secondary metabolites in CSF from 3 provinces of China using UPLC‐Q‐Orbitrap‐HRMS combined with chemometrics and 30 differential components were chosen and indentified. Among them, 5 compounds with the highest degree of difference were selected as marker compounds which were applied for the differentiation of CSF from various sources. Our work offered a research foundation for the quality control of CSF.